2023
DOI: 10.1108/cpoib-04-2022-0023
|View full text |Cite
|
Sign up to set email alerts
|

Framing biases and language choices: how the Japanese media broadcast foreign aid policy for Africa

Abstract: Purpose This paper aims to investigate how the Japanese media conveyed the country’s foreign aid policy and analyse how framing biases in the news differ depending on which language (either Japanese or English) was used in the broadcasts. Design/methodology/approach This study uses a qualitative single case-study design and conducts a content analysis. The study uses news videos about the fifth Tokyo International Conference on African Development aired on YouTube by the Japanese media using Japanese and Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…This is in agreement with previous researchers (Uccelli, 2023;Choi et al, 2023) who reported that proper use of language in a social activity presents socially accepted and authentic processes for participation in real-life activities. Language aspects like grammatical gender marking, politeness in the use of pronouns and use of first-person singular pronouns influence an individual's perceptions, actions and outcomes about an intended communication studies (Berman et al, 2022;Hatani, 2023). Because not many information literacy studies have done an in-depth examination of language use, these findings can be used as a benchmark for crafting suitably worded agricultural messages to enable SHFs understand information better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with previous researchers (Uccelli, 2023;Choi et al, 2023) who reported that proper use of language in a social activity presents socially accepted and authentic processes for participation in real-life activities. Language aspects like grammatical gender marking, politeness in the use of pronouns and use of first-person singular pronouns influence an individual's perceptions, actions and outcomes about an intended communication studies (Berman et al, 2022;Hatani, 2023). Because not many information literacy studies have done an in-depth examination of language use, these findings can be used as a benchmark for crafting suitably worded agricultural messages to enable SHFs understand information better.…”
Section: Discussionmentioning
confidence: 99%
“…Language aspects like grammatical gender marking, politeness in the use of pronouns and use of first-person singular pronouns influence an individual’s perceptions, actions and outcomes about an intended communication studies (Berman et al. , 2022; Hatani, 2023). Because not many information literacy studies have done an in-depth examination of language use, these findings can be used as a benchmark for crafting suitably worded agricultural messages to enable SHFs understand information better.…”
Section: Discussionmentioning
confidence: 99%